Nerve Biopsy In The Diagnosis Of Leporsy - Hazra B; Banerjee P P; Bhattacharyya N K; Gupta P N; Barbhunia J N; Sanyal S (Wolters Kluwer Medknow Publications, 1997)
Skin and nerve biopsies were done in 33 cases of different clinical types of leprosy selected from Dermatology OPD of Medical College and Hospitals, Calcutta during 1994-95. Histopathological results were compared with emphasis on the role of nerve biopsies in detection of patients with multibacillary leprosy. The evident possibility of having patients with multibacillary leprosy in peripheral leprosy with multiple drugs. It is found that skin and nerve biopsy are equally informative in borderline and lepromatour leprosy and is the only means to diagnose polyneuritic leprosy. Nerve biopsy appears to be more informative in the diagnosis of all clinical types of leprosy.